2014
DOI: 10.1371/journal.pone.0102060
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Whale Shark Occurrence at Their Fringe Oceanic Habitat

Abstract: Studies have shown that the whale shark (Rhincodon typus), a vulnerable large filter feeder, seasonally aggregates at highly productive coastal sites and that individuals can perform large, trans-boundary migrations to reach these locations. Yet, the whereabouts of the whale shark when absent from these sites and the potential oceanographic and biological drivers involved in shaping their present and future habitat use, including that located at the fringes of their suitable oceanic habitat, are largely unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…Past studies on the ecology and biology of whale sharks have suggested a relationship between their movements and environmental features, including sea surface temperature, chlorophyll a concentrations, bottom relief and ocean currents [3–12]. Commonly, environments with an optimal scenario for whale shark occurrence provide suitable conditions for primary and secondary productivity, as the main known purpose for whale shark aggregation is foraging [2,1315].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies on the ecology and biology of whale sharks have suggested a relationship between their movements and environmental features, including sea surface temperature, chlorophyll a concentrations, bottom relief and ocean currents [3–12]. Commonly, environments with an optimal scenario for whale shark occurrence provide suitable conditions for primary and secondary productivity, as the main known purpose for whale shark aggregation is foraging [2,1315].…”
Section: Introductionmentioning
confidence: 99%
“…Adult whale sharks are infrequently observed, and the majority of sightings have been recorded at oceanic locations, such as the Galapagos Islands [36], Baja California Sur [18,37], the Azores [12], St. Helena Island [38] and ASPSP ([25]; present study). However, complete information on the distribution of mature whale sharks, and on the location of mating and nursery grounds, if any, remains lacking, despite being crucial for the conservation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…This region has one of the highest densities of seamounts in the Northeast Atlantic (Morato et al, 2013). Several of these seamounts host commercially valuable pelagic and demersal fish species important for local fisheries (Morato et al, 2008b;Menezes et al, 2013) and act as foraging posts for sea turtles, seabirds, marine mammals, and large pelagic fishes (Santos et al, 2007;Morato et al, 2008b;Silva et al, 2013;Afonso et al, 2014b;Tobeña et al, 2016). However, with few exceptions (e.g., Hargreaves, 1975;Martin and Nellen, 2004), previous studies on acoustic backscatter distribution in the Azores have focused only in open ocean areas (e.g., Moore, 1950;McElroy, 1974;Smailes, 1976;Wade and Heywood, 2001).…”
mentioning
confidence: 99%
“…The Azores represent an important habitat for a wide range of migrating marine fauna ranging from seabirds (Monteiro et al, 1996), cetaceans , elasmobranchs (Vandeperre et al, 2014), or tuna (Pham et al, 2013) whose migrations are tightly linked to environmental factors (Amorim et al, 2009;Afonso et al, 2014;Prieto et al, in press;Tobeña et al, 2016;Druon et al, 2017). All these studies found SST and primary productivity or chlorophyll-a concentrations as the main environmental factors explaining the spatial distribution of large migratory species.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies found SST and primary productivity or chlorophyll-a concentrations as the main environmental factors explaining the spatial distribution of large migratory species. Additionally, geomorphologic characteristics and features such as bathymetric slope or distance to seamounts (Amorim et al, 2009;Afonso et al, 2014) have also been referred as important drivers of the distribution of large pelagic animals, highlighting the usefulness of the comprehensive review of the geomorphology of the Azores region (Perán et al, 2016).…”
Section: Discussionmentioning
confidence: 99%